Evaluation of medetomidine-tiletamine-zolazepam as a partially reversible field anesthesia combination for mesocarnivores - Fernando Nájera; Jamie L. Palmer; Stella F. Uiterwaal; Parami Peiris; Manuel Mata-Huete; Juan Francisco Sánchez; María Jesús Palacios; Rebeca Grande-Gómez; Luis Revuelta Rueda; Esther Descalzo; Jose Jimenez; Pablo Ferreras; et al. (PLoS ONE, 2026)
Anesthesia timing stages and physiologic variables during field anesthesia with medetomidine–tiletamine–zolazepam (MTZ), partially reversed with atipamezole, were evaluated in 142 free-living individuals from 11 mesocarnivore species, including stone marten ( Martes foina , n = 7; European badger ( Meles meles , n = 3); European polecat ( Mustela putorious , n = 1), Egyptian mongoose ( Herpestes ichneumon , n = 32), common genet ( Genetta genetta , n = 9), northern raccoon ( Procyon lotor , n = 29), Virginia opossum ( Didelphus virginiana , n = 27), red fox ( Vulpes vulpes , n = 18); coyote ( Canis latrans , n = 5), European wildcat ( Felis silvestris , n = 7); and bobcat ( Lynx rufus , n = 4). Intermittent live-capture operations took place in central, western, and south-central Spain and Missouri (USA) between April 2016 and August 2024. The dose of medetomidine administered ranged from 0.038–0.055 mg/kg, while that of tiletamine-zolazepam and atipamezole ranged from 2.74–4.17 mg/kg and 0.18–0.27 mg/kg, respectively. Induction times over all species were 2–7.4 minutes, while anesthesia times ranged from 36–53.56 minutes. Reversal time of the species ranged from 3–11.72 minutes and recovery times ranged from 4–44.8 minutes. During anesthesia episodes, there were no major patterns of disturbance in rectal temperature, respiratory rate, heart rate, and pulse oximetry derived hemoglobin oxygen saturation, although we did record a steady decrease of rectal temperature and heart rate over the course of the anesthesia in most animals. Based on the results obtained, MTZ dosages described produced safe physiological states and adequate anesthetic depth that facilitated minimally invasive procedures during handling of mesocarnivores in the field.